Polymer coated vermiculite-iron composites: Novel floatable magnetic adsorbents for water spilled contaminants - Machado, L. C. R. (2006)
Magnetic adsorbents based on vermiculite-iron have been prepared and characterized by magnetic measurements, BET surface area, Mössbauer spectroscopy, powder X-ray diffraction, scanning electron microscopy, thermogravimetric and differential scanning calorimetric analyses. These magnetic materials show two important features for the remediation of contaminated sites: (i) they float on water and can be used to adsorb/ absorb spilled oils and (ii) after adsorption they can be easily removed from the medium by a simple magnetic separation procedure. These magnetic materials have been coated/hydrophobized with polymers such as epoxy resin and polystyrene improving their oil remotion capacity, floatability and the chemical and mechanical resistance.